Experimental Induction of Friendship Jealousy: Comparing the Effects of Time versus Mental Coordination with an Interloper - Fernández, Ana María; Castro, Belén; Molina, Pablo; Cosmides, Leda; Burkett, Brandy (Psykhe, 2022)
Jealousy is an emotional response to the threat of losing a valued relationship. In this research, we revisit the proposal that jealousy in friendship is an evolved response to the threat of someone else replacing what is unique in this kind of relationship. Burkett (2009) found that most people identify mental coordination—responding to the world as you do—as the feature that makes their best friend uniquely valuable to them. We presented 305 Chilean participants with one of three hypothetical conditions, in which their best friend: i) spent most of their time with a new friend, ii) shared mental coordination with a new friend, or iii) spent most of their time and shared mental coordination with a new friend. We replicated the expected effect in this novel context: Friendship jealousy was evoked more strongly by the threat of losing mental coordination with a friend than by just losing time spent with them, and friendship jealousy was higher for women than to men. We discuss the implications of these findings in order to understand friendships evolutionary basis and psychology, as well as other close relationships, and other types of non-pathological jealousy.